2009
DOI: 10.1097/tp.0b013e3181ba6f85
|View full text |Cite
|
Sign up to set email alerts
|

GITR Blockade Facilitates Treg Mediated Allograft Survival

Abstract: BACKGROUND-Many models of transplant tolerance have been found to depend upon the induction of regulatory T cells (T-regs). Innate immune signals are known to down-regulate T-regs thereby augmenting immunity by abrogating regulatory T cell function. Such signals may also provide a barrier to transplantation tolerance mediated by T-regs. A number of cell surface molecules expressed by T-regs have been found to inhibit T-reg activity, the best characterized of which is the glucocorticoid-induced TNF receptor-rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 54 publications
0
15
0
1
Order By: Relevance
“…Our and other studies on in vivo GITR-triggering [15][16][17] or GITR −/− mice [18][19][20] provided evidence of a GITR involvement in development of the inflammatory/autoimmune processes, which was explained as a consequence of GITR-dependent higher activation level of effector T lymphocytes and lower regulatory activity of natural Treg cells. The present study suggests that the minor susceptibility of GITR −/− mice to inflammatory stimuli and the higher activation following GITR-triggering depends also on a different GITR-dependent ability of BMDC to stimulate T lymphocytes.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Our and other studies on in vivo GITR-triggering [15][16][17] or GITR −/− mice [18][19][20] provided evidence of a GITR involvement in development of the inflammatory/autoimmune processes, which was explained as a consequence of GITR-dependent higher activation level of effector T lymphocytes and lower regulatory activity of natural Treg cells. The present study suggests that the minor susceptibility of GITR −/− mice to inflammatory stimuli and the higher activation following GITR-triggering depends also on a different GITR-dependent ability of BMDC to stimulate T lymphocytes.…”
Section: Discussionmentioning
confidence: 78%
“…Several studies have indicated GITR plays an important role in autoimmune/inflammatory diseases [14][15][16][17]. Using GITR knockout (GITR −/− ) mice, we have demonstrated that GITR contributes to the in vivo development of the inflammatory response [18][19][20].…”
Section: Introductionmentioning
confidence: 96%
“…In a comprehensive study on the interaction between TNFSF members and TNFRSF members, Bossen et al demonstrated that mGITRL does not interact with hGITR receptor and that hGITRL does not interact with the mouse receptor (Bossen et al, 2006). Even if contrasting results have been recently reported (Sonawane et al, 2009), it seems that the GITRL/ GITR binding is species specific as also suggested by the lack of similarity between mouse and human GITR in the first cystein pseudorepeat of the extracellular domain . Indeed, important differences between the tridimensional structures of hGITRL and mGITR have been demonstrated by two independent groups performing crystallographic studies on both murine and human GITRL (Chattopadhyay et al, 2007;Zhou et al, 2008a,b).…”
Section: Hgitr and Gitrl Are Structurally Different From Their Respecmentioning
confidence: 99%
“…Many groups have observed in vitro that GITR stimulation abrogates Treg suppressive activity (46, 47), which may be partially explained by the direct effects on CD4+CD25− T cells described above, but experiments using mouse-specific anti-GITR antibodies in combined rat-mouse proliferation assays suggest that GITR signaling on both CD4+CD25+ and CD4+CD25− T cells is involved (47). In some in vivo models of transplant tolerance, it appears that GITR exerts its pro-inflammatory effects through CD4+CD25+ Tregs and not CD4+CD25− T cells (51), while other infectious, auto-immune, and transplant models implicate both (45, 47, 50, 52, 53). …”
Section: Both Cytokines and Cell Surface Molecules Modulate Treg Funcmentioning
confidence: 99%